Understanding professional development challenges of Chinese public health professionals: association and prediction analyses with data validity screening - Wang, Yingchen; Kong, Xiangran; Li, Fang; Zhao, Hongyan (Frontiers in Public Health, 2023)
Background Little is known about the public health professionals engaged in educating and training new or future researchers in public health. Research in this direction identifies their issues, concerns, challenges, and needs. This study focused on the professional development challenges of Chinese public health professionals. Methods Snowball sampling was utilized. A total of 265 public health professionals participated. An instrument of 6 dimensions (burnout, sleep issue, mood issue, friends’ support, exercise, and challenges) was developed, revised, and administered online. Two different approaches, the conventional and data screening approaches, were applied. The former started with item quality analyses, whereas the latter began with data quality checks. The chi-square tests of associations and logistic regressions were performed on both approaches. Results and discussion 19.25% of the participants were detected and deleted as careless respondents. Using both approaches, six professional development challenges except one (“Multidisciplinary learning”) were significantly associated with various demographic features. The two approaches produced different models though they converged sometimes. The latent variables of exercise predicted professional development challenges more frequently than other latent variables. Regarding correct classification rates, results from the data screening approach were comparable to those from the conventional approach. Conclusion The latent variables of exercise, such as “Exercise effects,” “Expectations of exercise,” and “Belief in exercise,” might be understudied. More research is necessary for professional development challenges using exercise as a multidimensional construct. Based on the current study, screening and deleting careless responses in survey research is necessary.